2016
DOI: 10.1080/09658211.2016.1205096
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and characteristics of memories of the future

Abstract: Recent research suggests that some imagined future events are encoded in memory, leading to the formation of "memories of the future". However, questions remain regarding the exact components of future event simulations that are encoded and the factors that determine their accessibility. To address these questions, the present study investigated memory for previously imagined future events using both free and cued recall tasks. The results showed that most future event simulations were successfully encoded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 44 publications
7
24
0
2
Order By: Relevance
“…Rehearsal ratings for future events were lower on average in Ernst and D'Argembeau (2017) than in the current study. The future events elicited in this study were rated fairly high on rehearsal, which, as previously noted, suggests that many of the future events may have previously been imagined/constructed and that participants may have retrieved memories of previously constructed future events (Jeunehomme & D'Argembeau, 2017;Szpunar, Addis, McLelland, & Schacter, 2013). found that repeated simulation of novel future events leads to future event representations becoming more detailed and perceived as more plausible.…”
Section: Consistent Withsupporting
confidence: 78%
“…Rehearsal ratings for future events were lower on average in Ernst and D'Argembeau (2017) than in the current study. The future events elicited in this study were rated fairly high on rehearsal, which, as previously noted, suggests that many of the future events may have previously been imagined/constructed and that participants may have retrieved memories of previously constructed future events (Jeunehomme & D'Argembeau, 2017;Szpunar, Addis, McLelland, & Schacter, 2013). found that repeated simulation of novel future events leads to future event representations becoming more detailed and perceived as more plausible.…”
Section: Consistent Withsupporting
confidence: 78%
“…Imagined events that were more detailed, more plausible, and more familiar were more likely to be remembered. Another study showed that imagined future events that could be recalled without the help of cues (i.e., in a free recall task) were rated as more personally important and involved more intense emotions 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Antes de avanzar en el desarrollo del presente artículo, explicaremos el concepto de EFT y algunas de las investigaciones relacionadas con este tipo de imágenes mentales (Jeunehomme & D'Argembeau, 2017;Lehner & D'Argembeau, 2016). Esto facilitará la comprensión de los siguientes apartados donde desarrollaremos los estudios sobre el engaño centrados en intenciones.…”
Section: Detección Del Engaño En Intencionesunclassified
“…Ulteriores estudios relacionados con la simulación de hechos futuros muestran que los detalles de una escena imaginada, la plausibilidad de que suceda y la familiaridad de las personas imaginadas, aparecen como importantes predictores en el almacenamiento en la memoria y posterior recuperación (McLelland, Devitt, Schacter, & Addis, 2015). Una parte esencial en la memorización y recuperación a posteriori de una simulación futura, lo constituyen las personas, los lugares y las emociones (Barsics, Van der Linden, & D'Argembeau, 2016;McLelland et al, 2015;Robin, Wynn, & Moscovitch, 2015;Szpunar, Addis, & Schacter, 2012), por encima de los objetos o las acciones (Jeunehomme & D'Argembeau, 2017). Una vez detalladas algunas de las características del EFT, a continuación entraremos ya a desglosar las diferentes aproximaciones en las investigaciones relacionadas con la detección del engaño en intenciones.…”
Section: Pensamiento Episódico Futuro (Eft)unclassified